Motives, personality and subjective well-being in volunteering - Cabrera-Darias, Marcial; Marrero-Quevedo, Rosario J. (Anales de Psicología / Annals of Psychology, 2015)
In this study, the aim was to analyze the relationships between individuals’ motivation for to participate in volunteering, personality traits and subjective well-being. Data collection was conducted through paper-and-pencil and on-line tests. A total of 153 adults, aged 17-65 years old, completed the instruments. The results showed that previous motivations differed between the two groups of volunteers. Correlational analyzes indicated that motivations, as requested by the organization, personal circumstances or life experiences, were associated with life satisfaction and negative affect in on-line volunteers; whereas that to do something useful or feelings of peace were the motives associated to well-being for volunteers who completed the test in paper and pencil. Personality traits, mainly neuroticism, showed more consistent relationships with well-being that the motivations in both groups of volunteers. Regression analyzes indicated that the facets of extraversion, gregariousness, warmth and activity were the strongest predictors of well-being for the volunteers who made the tests on paper and pencil; whereas that the facet of conscientiousness discipline and the emotional stability predicted well-being for the volunteers who completed the test on-line. These findings suggest that there are different profiles of volunteers that could be determining their participation in various activities or collectives. In addition, personal traits have shown to have a greater effect on well-being that the motivations to participate in volunteering.